Perfectly Green Organocatalysis： Quaternary Ammonium Base Triggered Cyanosilylation of Aldehydes - 温叶倩 梁梦伟 王忆铭 任伟民 吕小兵 (Chinese journal of chemistry, 2012)
Quaternary ammonium bases, such as aqueous （CH3）4NOH, were found to be an extraordinarily efficient cata-lyst for cyanosilylation of aldehydes. The addition reaction of trimethylsilyl cyanide （TMSCN） to equivalent alde-hydes could proceed smoothly with turnover frequency （TOF） up to 3000000 h l and in near 100% yield under solvent-free conditions. These organic catalysts also tolerated various aldehydes including aromatic, aliphatic and a,fl-unsaturated aldehydes. This process perfectly conforms to the features of green chemistry： no waste regarding side-products and unconverted reactants, solvent-free, excellent catalytic activity, and no requirement for separa- tion.